A study of students’ perceptions of mathematics learning situations - 김소민; 서보억; 고호경; 허난 (수학교육, 2024)
This study investigated how Korean elementary, middle, and high school students perceive mathematics learning situations to determine whether the mathematics classes provided in schools met the standards of a highquality educational experience. Using a comprehensive survey that considers both formal and implementation aspects of mathematics classes, responses from 15,418 students were analyzed to gain insights into their views on the classroom environment, instructional methods, and overall learning experience. The results indicate that as students advance in grade level, their perceptions of mathematics learning situations become increasingly negative, and mathematics classes are still perceived as being teacher-centered. Additionally, it was found that mathematical manipulatives and technological tools are not being effectively utilized, and that students’ learning experiences are influenced by class size and the availability of mathematics subject-exclusive classrooms. Based on these findings, several recommendations were made to improve the quality of mathematics education and enhance students’ perceptions: implementing teaching methods that increase student engagement in learnercentered classes, providing opportunities for active and diverse use of teaching aids and technological tools beyond simple calculations, maintaining appropriate class sizes, and expanding the use of mathematics subject-exclusive classrooms. These considerations are crucial for creating a more engaging and effective mathematics learning environment that aligns with evolving educational standards and meets students’ needs. The findings of this study provide actionable insights for educators and policymakers aiming to improve the quality of mathematics education in Korea.
Keywords: Students’ perceptions; School mathematics classes; Good mathematics classes; Mathematics learning situation; Mathematics education improvement; 학생들의 인식; 학교 수학 수업; 좋은 수학 수업; 수학 학습 상황; 수학교육 개선